Comparative analysis on the implementation of R.A. 8550 on fishing gears among the three selected Coastal communities of Davao City, Philippines - Baldoza, Dianne Margarette N.; Agustin, Nicasio Angelo J.
The study was a baseline study on the implementation of Section 90 (Use of Active Gear in the Municipal Waters and Bays and Other Fishery Management Areas) under the Philippine Fisheries Code of 1998 or Republic Act 8550. The study generally aimed to compare the effects of the implementation of RA 8550's provision on fishing gears to the income and other economic activities of the municipal fisherfolks in Matina Aplaya, Lasang, and Lizada. Its specific objectives were to determine and compare the level of awareness of the respondents, and to describe and compare the fishery resources, fishing gears, fishing income, and other economic activities before and after the implementation of R.A. 8550 (1995-1998 and 1999-2003). The study used informal interview with local key infomrants. A survey questionnaire was utilized for the randomly selected registered municipal fisherfolks. The results of the study show that there was a decline on the conditions of the municipal fishing waters, fish species, fish supply, fish catch, and fishing income. Engagement in other economic activities was the most viable option for the municipal fisherfolks to cope with their poverty. Thus, it would be best to provide and help the fisherfolks to have other sources of income besides fishing. More educational information campaign must be conducted on advocating passeive fishing gears for the municipal fisherfolks. The implementation of Section 90 monitoring must be strict to deter any violators.
Thesis, Undergraduate (BS Economics)--University of the Philippines, Mindanao